An oil-ice semi-solid phase co-precipitation process for synthesizing Prussian blue cathode materials
The synthesis of Prussian blue battery positive electrode material through the oil-ice semi-solid phase co-precipitation process has solved the problems of excessive crystallization, high defect degree and high production cost in the prior art, and achieved the preparation and electrochemical performance of high-quality materials Improvement.
Patent Information
- Application Number
- CN202411168358.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-08-23
AI Technical Summary
The existing synthesis method of Prussian blue battery positive electrode material has problems such as excessive crystallization water, high degree of defects and high production costs.
Using the oil-ice semi-solid phase co-precipitation process, the co-precipitation reaction is achieved by dissolving the metal cyanate salt in water and freezing it into ice cubes, and the organometallic salt is dissolved in an oil-based organic solvent with a density greater than water, so as to achieve a co-precipitation reaction and reduce water and other chemical agents.
It effectively reduces the crystal water content and defects of the material, reduces production costs, and improves electrochemical performance and cycle stability.
Smart Images

Figure CN118833832B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of batteries, and in particular relates to an oil-ice semi-solid phase co-precipitation synthesis method for a Prussian blue battery positive electrode material. Background Art
[0002] Positive electrode materials are important components of batteries. Prussian blue materials (PBAs) have become one of the most promising battery positive electrode material systems due to their excellent electrochemical performance and cost-effectiveness. Among the existing synthesis methods, the solid phase ball milling method does not require the introduction of water, but it has the disadvantages of insufficient reaction, easy mixing of impurities and extremely high equipment requirements, so it is difficult to synthesize high-quality crystals; although the materials produced by the acid hydrolysis single iron source method have high electrochemical properties, the application of this method is also limited by the fact that it is very easy to produce toxic gas cyanide. The traditional liquid phase coprecipitation method is simple to operate, the reaction is complete, and the products are environmentally friendly. However, this method requires a large amount of water to dissolve the reactants to achieve mass production, and it is necessary to continuously introduce rare gases to prevent the material from being oxidized. A large amount of chelating agents and surfactants are also required to reduce the chemical reaction rate. It also requires instruments such as peristaltic pumps to accurately control the feed rate. In addition, the post-treatment cost of the wastewater generated by this method is also high. At the same time, the crystals produced by this method cannot fully nucleate and grow, and there are many internal defects (vacancies and crystal water) in the material, so it is difficult to synthesize high-quality crystals and have poor electrochemical properties. In summary, this synthesis method usually leads to high material cost and poor electrochemical performance, and is not completely suitable for the actual production of PBAs. Summary of the invention
[0003] The purpose of the present invention is to solve the problems of existing synthetic PBAs materials such as high crystal water content, high degree of defects and high production cost, and to provide an oil-ice semi-solid phase co-precipitation process for synthesizing Prussian blue positive electrode materials. The process is a new co-precipitation method that utilizes oil-ice semi-solid phase co-precipitation to effectively reduce the use of water, complexing agents, surfactants and rare gases, simplify production equipment, and also provide a method for preserving PBAs materials, ultimately reducing the reaction rate, facilitating the full nucleation and growth of crystal nuclei, and effectively reducing production costs.
[0004] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0005] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material, the process comprising the following steps:
[0006] Step 1, completely dissolving the organic metal salt in an oil-based organic solvent having a density greater than that of water;
[0007] Step 2, completely dissolving the metal cyanate in water, and then freezing it into a plurality of ice cubes; wherein the amount of the organic metal salt is the same as the amount of the metal cyanate;
[0008] Step 3, adding the ice cubes obtained in step 2 to the oil-based solution obtained in step 1 at a certain time interval for multiple times, and waiting for the two to react completely; whether the reaction is complete or not can be judged as follows: first, this reaction is at the interface, and the reaction can be considered complete when there is no obvious phenomenon at the interface, and the precipitate generated when the reaction is complete will settle into the bottom solvent; second, the upper layer is ice that will have color after melting into water (such as sodium ferrocyanide will appear yellow when dissolved in water), and the reaction can be considered complete when the color fades or becomes lighter.
[0009] Step 4: After the product obtained in step 3 is stored for a period of time, it is washed with a certain mass fraction of an organic solution soluble in water, centrifuged, and vacuum dried to obtain a Prussian blue battery positive electrode material. Storage for a period of time is conducive to the full growth of the unreacted grains; vacuum drying is required after washing. Under normal circumstances, the boiling point of organic solvents soluble in water is relatively low. If an organic solvent with a high boiling point is selected without restriction, it will not be conducive to removal. Too high a temperature will destroy the Prussian blue crystals. In addition, some metal cyanates may not react completely and need to be removed in time. Metal cyanates are insoluble in organic solvents but soluble in water, so a certain mass fraction of an organic solution soluble in water is required for washing;
[0010] Step 5: The mixed solution after centrifugation in step 4 is allowed to stand for a period of time. After the mixed solution is treated in a certain manner, the lower layer of the solution can be reused in step 1, and the upper layer of the solution can be reused in step 2.
[0011] Further, in step 1, the metal in the organic metal salt includes one or more combinations of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb; the organic salt in the organic metal salt includes one or more combinations of stearate, isooctanoate, bismuth salt, fumarate, acetylacetonate, bismuth tetrafluoroborate, bismuth hexafluorophosphate, trifluoromethanesulfonate, and pyridinium acetate, wherein the organic salts used for different metal ions need to be consistent.
[0012] Further, in step 1, the oil-based organic solvent having a density greater than that of water includes dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, dimethyl terephthalate, dimethyl adipate, diethyl adipate, dimethyl sebacate, dimethyl maleate, dimethyl fumarate, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, benzyl acetate, benzyl propionate, benzyl butyrate, benzyl valerate, methyl salicylate, ethyl salicylate, methyl chloroacetate, ethyl chloroacetate, methyl bromoacetate, bromoacetate, ethyl ... A combination of one or more of ethyl acetate, methyl nitrobenzoate, ethyl nitrobenzoate, methyl dichloroacetate, ethyl dichloroacetate, methyl trichloroacetate, ethyl trichloroacetate, tributyl phosphate, triphenyl phosphate, methyl stearate, ethyl stearate, methyl oleate, ethyl oleate, methyl linoleate, ethyl linoleate, methyl linoleate, ethyl linolenate, methyl laurate, ethyl laurate, methyl myristate, ethyl myristate, methyl palmitate, ethyl palmitate, methyl sorbate, ethyl sorbate, propyl gallate, and butyl gallate.
[0013] Furthermore, in step 2, the metal cyanate includes one or a combination of sodium ferrocyanide, sodium ferrocyanide, potassium ferrocyanide, potassium ferrocyanide, potassium cobalt cyanide, and potassium nickel cyanide.
[0014] Furthermore, in step 2, the shape of the ice cube includes one or more combinations of a cube, a cuboid, a sphere, a cylinder, and a cone.
[0015] Furthermore, in step 2, the freezing temperature is between -100°C and -5°C.
[0016] Furthermore, in step 3, the time interval includes a combination of one or more of 0 min (all added at one time), 2 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min.
[0017] Furthermore, in step 4, the storage period includes one of 0h (not storing), 1h, 2h, 5h, 10h, 12h, 15h, 20h, 24h, 36h, and 48h.
[0018] Furthermore, in step 4, the certain mass fraction includes one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%; the water-soluble organic solution includes a combination of one or more of ethanol solution, acetone solution, n-propanol solution, and isopropanol solution.
[0019] Furthermore, in step 5, the standing period includes 2h, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h or 24h; the certain treatment includes a combination of one or more methods of adsorption, filtration, extraction, separation and distillation.
[0020] A Prussian blue positive electrode material prepared by the above method, wherein the chemical formula of the positive electrode material is A x M1[M2(CN)6] 1-y nH2O, wherein 1≤x≤2, 0≤y<1, 0<n≤3.5, A includes Na and / or K, the M1 site includes one or a combination of Sc, Ti, V, Cr, Co, Ni, Cu, Zn, Ga, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb; the M2 site includes one or a combination of Fe, Mn, Co and Ni. The overall size of the positive electrode material particles is between 1 μm and 10 μm.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The Prussian blue cathode material provided by the present invention is prepared by the oil-ice co-precipitation synthesis method in a low-water environment, which is beneficial to reducing the crystal water content of the material. Compared with other synthesis processes, the cathode material provided by the present invention has few defects, uniform particles, and excellent dispersion.
[0023] (2) Compared with the conventional liquid phase co-precipitation process, the oil-ice co-precipitation synthesis process adopted in the present invention uses a small amount of water, which is beneficial to further reduce the use of water and the cost of wastewater post-treatment.
[0024] (3) The present invention effectively inhibits the ionization of reactants by introducing an immiscible oil-ice system, thereby reducing the reaction rate and allowing the crystals to fully nucleate and grow. The prepared positive electrode material has a particle size of micrometer particles, which helps to reduce stress accumulation at the grain boundary and electrode-electrolyte interface side reactions during the cycle as a battery material, thereby improving the electrochemical cycle stability.
[0025] (4) The PBAs prepared by the present invention are all micron-sized, with less difficulty in separation, more stable structure, high crystallinity, and stable electrochemical performance.
[0026] (5) During the synthesis process of the present invention, part of the raw materials are dissolved in water and then frozen into ice cubes, which are then added to an organic oil-based solvent. The ice cubes absorb heat during the melting process, lowering the temperature of the reaction system, thereby reducing the reaction rate and forming high-quality crystal nuclei, so that the Prussian blue crystals have better cycle stability as a battery positive electrode material.
[0027] (6) In the synthesis process of the present invention, no complexing agent or surfactant is used, which effectively reduces the production cost.
[0028] (7) Compared with the liquid phase co-precipitation synthesis process, the present invention is advantageous in reducing the synthesis time, does not require the use of instruments such as peristaltic pumps to control the feed rate, has lower equipment requirements, and reduces operating costs and difficulty.
[0029] (8) The materials produced by traditional liquid phase co-precipitation are completely in contact with water, which has a strong oxygen dissolving capacity. If the inert gas is not continuously passed, the materials will be oxidized. However, the materials produced by the present invention react at the interface between oil and water as the ice cubes dissolve into water. Compared with traditional liquid phase co-precipitation, the materials produced by the present invention are not completely in contact with water. The products are finally precipitated at the bottom of the organic solvent, which is effectively isolated from contact with the air, preventing impurities in the air from entering the materials and oxidizing the materials. This not only effectively reduces the use of inert gas, but also enables the materials to be stored for a long time.
[0030] (9) The mixed solution finally separated by the present invention contains a large amount of sodium salt and / or potassium salt, which can be repeatedly recycled after various physical treatments, thereby increasing economic benefits and effectively reducing costs. In addition, the residual sodium salt and / or potassium salt provide a sodium and / or potassium source during the synthesis process, making the produced material rich in sodium / potassium and improving the electrochemical properties of the material.
[0031] (10) The battery prepared with the positive electrode material provided by the present invention has a high cycle capacity retention rate, does not show obvious changes in the standard number of cycles, has excellent quality, and meets industry standards. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is a SEM image of the PBAs material synthesized in Example 1 of the present invention;
[0033] Figure 2 This is the XRD pattern of the PBAs material synthesized in Example 1 of the present invention;
[0034] Figure 3 This is a rate performance diagram of the PBAs material synthesized in Example 1 of the present invention;
[0035] Figure 4 This is a cycle performance diagram of the PBAs material synthesized in Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0037] Example 1
[0038] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material comprises the following steps:
[0039] Metal cyanate is dissolved in water and then frozen into ice cubes of a certain shape, and metal organic ion salts are dissolved in an oil-based organic solvent with a density greater than that of water.
[0040] Among them, the metal cyanate is 10mmol sodium ferrocyanide, dissolved in 50ml water, divided into 10 portions and loaded into a cube mold, and frozen at -20℃ for a period of time; the metal organic ion salt is 10mmol ferrocene, dissolved in 50ml of oil-based organic solvent dimethyl phthalate.
[0041] Subsequently, after being completely frozen, ice cubes were added to the dimethyl phthalate solution in 10 times, with a time interval of 5 minutes, and after the reaction was complete, it was allowed to stand for 12 hours. The obtained material was washed with a 20% ethanol solution by volume, vacuum dried at 150°C for 12 hours, and sieved in a drying oven to obtain a Prussian blue battery positive electrode material. The washing liquid was filtered, and after standing for 12 hours, liquid separation was performed, and the separated liquid was reserved for use in Example 2. The particle size of the material prepared in Example 1 was between 4 and 6 μm.
[0042] Example 2
[0043] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material comprises the following steps:
[0044] Metal cyanate is dissolved in water and then frozen into ice cubes of a certain shape, and metal organic ion salt is dissolved in an oil-based organic solvent.
[0045] Among them, the metal cyanate is 10mmol sodium ferrocyanide, which is dissolved in 50ml water (part of it is taken from the upper clear liquid after separation in Example 1, if it is insufficient, add more to 50ml), divided into 10 parts and loaded into a cube mold, and frozen at -20℃ for a period of time; the metal ion salt is 10mmol ferrocene, which is dissolved in 50ml oil-based organic solvent (part of it is taken from the lower layer of oil-based organic solvent in Example 1, if it is insufficient, add more to 50ml).
[0046] Subsequently, after being completely frozen, ice cubes were added to the dimethyl phthalate solution in 10 times, with a time interval of 5 minutes, and the reaction was completely allowed to stand for 12 hours. The obtained material was washed with a 20% volume fraction ethanol solution, vacuum dried at 150° C. for 12 hours, and sieved in a drying oven to obtain a Prussian blue battery positive electrode material.
[0047] Example 3
[0048] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material comprises the following steps:
[0049] Metal cyanate is dissolved in water and then frozen into ice cubes of a certain shape, and metal organic ion salt is dissolved in an oil-based organic solvent.
[0050] The metal cyanate is 20 mmol potassium ferrocyanide, which is dissolved in 100 ml water, divided into 20 portions and loaded into a spherical mold, and frozen at -50°C for a period of time; the metal ion salt is 20 mmol manganese acetylacetonate, which is dissolved in 100 ml of an oil-based organic solvent benzyl acetate.
[0051] Subsequently, after being completely frozen, the ice cubes were added to the benzyl acetate solution 20 times at a time interval of 10 minutes. After the reaction was complete, the obtained material was immediately washed in a 10% acetone solution, vacuum dried at 170°C for 15 hours, and sieved in a drying oven to obtain a Prussian blue battery positive electrode material. The washing liquid was filtered, left to stand for 12 hours, and then separated. The separated liquid was used in Example 4.
[0052] Example 4
[0053] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material comprises the following steps:
[0054] Metal cyanate is dissolved in water and then frozen into ice cubes of a certain shape, and metal organic ion salt is dissolved in an oil-based organic solvent.
[0055] Among them, the metal cyanate is 20mmol potassium ferrocyanide, which is dissolved in 100ml of water (part of it is taken from the upper clear liquid after separation in Example 3, if it is insufficient, add more to 100ml), divided into 20 portions and loaded into spherical molds, and frozen at -50℃ for a period of time; the metal ion salt is 20mmol manganese acetylacetonate, which is dissolved in 100ml of oil-based organic solvent benzyl acetate (part of it is taken from the lower layer of oil-based organic solvent in Example 3, if it is insufficient, add more to 100ml).
[0056] Subsequently, after being completely frozen, the ice cubes were added to the benzyl acetate solution in 20 times with a time interval of 10 minutes. After the reaction was complete, the obtained material was immediately washed in a 10% acetone solution, vacuum dried at 170°C for 15 hours, and sieved in a drying oven to obtain a Prussian blue battery positive electrode material.
[0057] Example 5
[0058] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material comprises the following steps:
[0059] Metal cyanate is dissolved in water and then frozen into ice cubes of a certain shape, and metal organic ion salt is dissolved in an oil-based organic solvent.
[0060] Among them, the metal cyanate is 10mmol potassium cobalt cyanide, which is dissolved in 50ml water, put into a spherical mold after complete dissolution, and frozen at -20℃ for a period of time; the metal ion salt is 10mmol nickelocene hexafluorophosphate, which is dissolved in 50ml of oil-based organic solvent ethyl trichloroacetate.
[0061] Then, after being completely frozen, ice cubes were added to the ethyl trichloroacetate solution, and after being completely reacted, the mixture was left for 48 hours. The obtained material was washed in a 10% n-propanol solution, vacuum dried at 150° C. for 24 hours, and sieved in a drying oven to obtain a Prussian blue battery positive electrode material. The washing liquid was filtered, left to stand for 12 hours, and then separated. The separated liquid was used in Example 6.
[0062] Example 6
[0063] An oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material comprises the following steps:
[0064] Metal cyanate is dissolved in water and then frozen into ice cubes of a certain shape, and metal organic ion salt is dissolved in an oil-based organic solvent.
[0065] Among them, the metal cyanate is 10mmol potassium cobalt cyanide, which is dissolved in 50ml of water (part of it is taken from the upper clear liquid after separation in Example 5, if it is insufficient, add more to 5ml), and after it is completely dissolved, it is put into a spherical mold and frozen at -20℃ for a period of time; the metal ion salt is 10mmol nickelocene hexafluorophosphate, which is dissolved in 50ml of an oil-based organic solvent ethyl trichloroacetate (part of the ethyl trichloroacetate is taken from the lower layer of the oil-based organic solvent in Example 5, if it is insufficient, add more to 50ml).
[0066] Subsequently, after being completely frozen, ice cubes are added to an ethyl trichloroacetate solution, and after being completely reacted, the mixture is left for 48 hours. The obtained material is washed in a 10% n-propanol solution, vacuum dried at 150° C. for 24 hours, and sieved in a drying oven to obtain a Prussian blue battery positive electrode material.
[0067] The obtained Prussian blue cathode material (70 wt%), conductive carbon (20 wt%) and binder (polyvinylidene fluoride, PVDF) (10 wt%) were mixed in NMP solvent to form a slurry to prepare the PBAs working electrode. The prepared slurry was then coated on aluminum foil and dried in a vacuum oven at 150 °C overnight. The electrode was then cut into 14 mm diameter round pieces containing about 1.90 mg cm -2 The CR2032 button cell was assembled in an Ar-filled glove box (O2<0.01ppm, H2O<0.01pm) to prepare the working electrode, Na foil as the negative electrode, 1 mol / L sodium perchlorate, EC:PC volume ratio of 1:1, and 5% FEC as the electrolyte.
[0068] Tested at room temperature, after three cycles of activation at 0.2C, the following data were obtained by 1C cycle test:
[0069]
Claims
1. An oil-ice semi-solid phase co-precipitation process for synthesizing Prussian blue cathode materials, characterized in that: The process comprises the following steps: Step 1, completely dissolving an organic metal salt in an oil-based organic solvent having a density greater than that of water; the metal in the organic metal salt comprises one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb; the organic salt in the organic metal salt comprises one or more of stearate, isooctanoate, bismuth salt, fumarate, acetylacetonate, bismuth tetrafluoroborate, bismuth hexafluorophosphate, trifluoromethanesulfonate and pyridinium acetate, wherein the organic salts used for different metal ions must be consistent; Step 2, completely dissolving the metal cyanate in water, and then freezing it into a plurality of ice cubes; wherein the amount of the organic metal salt is the same as the amount of the metal cyanate; the metal cyanate comprises one or a combination of sodium ferrocyanide, sodium ferrocyanide, potassium ferrocyanide, potassium ferrocyanide, potassium cobalt cyanide, and potassium nickel cyanide; Step 3, adding the ice cubes obtained in step 2 directly or adding them several times at a certain time interval to the oil solution obtained in step 1, and wait for the two to react completely; Step 4: directly or after storing for a period of time, wash the product obtained in step 3 with a water-soluble organic solution having a certain mass fraction, centrifuge, and vacuum dry to obtain a Prussian blue positive electrode material.
2. The oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material according to claim 1, characterized in that: In step 1, the oil-based organic solvent having a density greater than that of water includes dimethyl phthalate, diethyl phthalate, dibutyl phthalate, dioctyl phthalate, dimethyl terephthalate, dimethyl adipate, diethyl adipate, dimethyl sebacate, dimethyl maleate, dimethyl fumarate, methyl benzoate, ethyl benzoate, propyl benzoate, butyl benzoate, benzyl acetate, benzyl propionate, benzyl butyrate, benzyl valerate, methyl salicylate, ethyl salicylate, methyl chloroacetate, ethyl chloroacetate, methyl bromoacetate, bromoacetic acid The invention can be selected from the group consisting of ethyl ester, methyl nitrobenzoate, ethyl nitrobenzoate, methyl dichloroacetate, ethyl dichloroacetate, methyl trichloroacetate, ethyl trichloroacetate, tributyl phosphate, triphenyl phosphate, methyl stearate, ethyl stearate, methyl oleate, ethyl oleate, methyl linoleate, ethyl linoleate, methyl linoleate, ethyl linoleate, methyl laurate, ethyl laurate, methyl myristate, ethyl myristate, methyl palmitate, ethyl palmitate, methyl sorbate, ethyl sorbate, propyl gallate, and butyl gallate.
3. The oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material according to claim 1, characterized in that: In step 2, the shape of the ice cube includes one or more combinations of cube, cuboid, sphere, cylinder and cone.
4. The oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material according to claim 1, characterized in that: In step 2, the freezing temperature is between -100°C and -5°C.
5. The oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material according to claim 1, characterized in that: In step 3, the time interval includes one or more combinations of 2 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, and 60 min.
6. The oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material according to claim 1, characterized in that: In step 4, the storage period includes one of 1h, 2h, 5h, 10h, 12h, 15h, 20h, 24h, 36h, and 48h.
7. The oil-ice semi-solid phase co-precipitation process for synthesizing a Prussian blue cathode material according to claim 1, characterized in that: In step 4, the certain mass fraction includes one of 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, and 50%; the water-soluble organic solution includes a combination of one or more of ethanol solution, acetone solution, n-propanol solution, and isopropanol solution.
8. A Prussian blue positive electrode material prepared by the process according to any one of claims 1 to 7, characterized in that: The chemical formula of the positive electrode material is A x M1[M2(CN)6] 1-y nH2O, wherein 1≤x≤2, 0≤y<1, 0<n≤3.5, A comprises Na and / or K, the M1 site comprises one or a combination of Sc, Ti, V, Cr, Co, Ni, Cu, Zn, Ga, Y, Zr, Nb, Mo, Ru, Rh, Pd, Ag, Cd, In, Sn, La, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm and Yb; and the M2 site comprises one or a combination of Fe, Mn, Co and Ni.
Citation Information
Patent Citations
Preparation method of Prussian blue analogue sodium ion battery positive electrode material
CN116588953A
Solid-phase synthesis method of single-crystal Prussian blue sodium battery positive electrode material
CN117448935A